Majlis Pusat Kebajikan Semalaysia / Nurul Zafirah Abu Samah - Abu Samah, Nurul Zafirah (University Technology MARA Sarawak, 2016)
Majlis Pusat Kebajikan SeMalaysia (MPKSM) was established in 1946. The original name for MPKSM is Majlis Pusat Kebajikan Malaya. Central Welfare Council was established after the Second World War in order to help those who need help as the result of the effects of the war (Jamir, 2013). In the early stage of setting up the Central Welfare Council, it members were appointed by the Government. The first president of Central Welfare Council was the wife of the Secretary General at that time, namely Mrs. A.T. Newboult. At the same time, the Central Welfare Council also has a welfare committee at the state and district level for help and run the charity walk. Members of the Central Welfare Council at the state and district level will also appointed by the government. Besides that, the District Officers was appointed as the Chairman while the assistant of District Officers was appointed as the secretary of the Central Welfare Council at the district level.